(untitled) (Biological Sciences - PJSIR, 2006)
The dissolution of chalcopyrite with hydrogen peroxide in sulphuric acid solution was investigated. The influence of temperature, stirring speed, concentrations of hydrogen peroxide and sulphuric acid, as well as the particle size of chalcopyrite were studied. Increase in the concentration of sulphuric acid had a positive effect on the dissolu- tion of the chalcopyrite. Stirring speed had a negative effect on the dissolution of chalcopyrite as it enhanced the decomposition of hydrogen peroxide. The dissolution process was found to follow a shrinking-core model, with sur- face chemical reaction as the rate determining step. This is in agreement with the activation energy of 39 kJ/mol, and a linear relationship between the rate constant and the reciprocal of the particle size. The dissolution process was postulated to be electrochemical in nature.